Assessing Environmental Performance of a Circular Business Modelusing Business Model Life Cycle Assessment A Case Study of a Sharing Service for Power Tools - Holzhausen, Frida; Troedsson, Linn (My University, 2023)
Climate change is becoming more and more inevitable and the pressure to act is higher than ever. While facing a growing world population and increasing con- sumption, production, and consumption patterns must become more sustainable. To counteract climate change, there is a need for business models that separate resource use and economic profit. One such type of model is the circular business model. By looping the resources in a non-finite system characterized by reuse and recycling, we can achieve decoupling. Circular business models can however be difficult to quantify and thus the actual climate impact compared to a linear counterpart becomes difficult to estimate in many cases. LCA is a tool that has been used in recent years to calculate the cli- mate impact of a product’s total life cycle. To apply this measurement method to an entire business model, BM-LCA was developed, which includes the use phase in the calculation and then relates the environmental impact to the profit. In this study, a BM-LCA is conducted on a case company that provides a subscription- sharing service for power tools. The BM-LCA is focused on one of the products, a percussion drill, and the locker depot holding all the tools. The method of the study consisted of information-gathering meetings with the case company as well as a literature study of relevant theory. It was found that the locker depot had a significant environmental impact and that a change in its material would have a significant effect on the emissions per profit. Additionally, the lifetime of the product was found to be significant as well as the user behavior which was found to be hard to estimate. Lastly, it was concluded that the BM-LCA did highlight valuable hot spots in the business model and that some changes could have a large impact on the final climate footprint of the product service offering. The study resulted in the following recommendations for the case company: Increase the lifetime of the product, reduce the weight and consider another material for the locker depot, increase the number of subscribers, consider partnerships with other actors in the ecosystem, lobby for a change in consume and considerhow the inconveniences related to sharing can be overcome.
Keywords: BM-LCA; circular economy; circular business models; consumption; sharing economy; business model assessment; life cycle assessment; product-service-system; production